2011
DOI: 10.1002/rcm.5282
|View full text |Cite
|
Sign up to set email alerts
|

Continuous analysis of δ18O and δD values of water by diffusion sampling cavity ring‐down spectrometry: a novel sampling device for unattended field monitoring of precipitation, ground and surface waters

Abstract: A novel sampling device suitable for continuous, unattended field monitoring of rapid isotopic changes in environmental waters is described. The device utilises diffusion through porous PTFE tubing to deliver water vapour continuously from a liquid water source for analysis of δ¹⁸O and δD values by Cavity Ring-Down Spectrometry (CRDS). Separation of the analysed water vapour from non-volatile dissolved and particulate contaminants in the liquid sample minimises spectral interferences associated with CRDS analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 28 publications
(58 reference statements)
0
73
0
Order By: Relevance
“…Since invention of the automated collector, laser absorption spectrometers have been developed and advocated for analysis of precipitation samples in the field (Berman et al, 2009;Munksgaard et al, 2011 H, respectively, in a sample P (Coplen, 2011). Commonly, an extraneous numerical factor of 1000 is added to this definition.…”
Section: Precipitation Isotope Collectors and Isotope Analysismentioning
confidence: 99%
“…Since invention of the automated collector, laser absorption spectrometers have been developed and advocated for analysis of precipitation samples in the field (Berman et al, 2009;Munksgaard et al, 2011 H, respectively, in a sample P (Coplen, 2011). Commonly, an extraneous numerical factor of 1000 is added to this definition.…”
Section: Precipitation Isotope Collectors and Isotope Analysismentioning
confidence: 99%
“…Second, the L2120-i has been widely used to measure δ 18 O-H 2 O and δ 2 H-H 2 O values in situations where background variation could be relevant to the calibration procedures and/or the fundamental measurements. Examples include applications to measurements of liquid water in precipitation (Munksgaard et al, 2011), plant water (West et al, 2011), soil water (Herbstritt et al, 2012), and seawater (Munksgaard et al, 2012), as well as water vapor in the terrestrial boundary layer (Berkelhammer et al, 2013) and marine boundary layer (Steen-Larsen et al, 2014). Third, it has recently been shown that the L2120-i measurements are highly sensitive to the N 2 / O 2 , N 2 / CO 2 , and CO 2 / O 2 composition of the background gas and that the magnitude of the sensitivity is relevant to many observational and experimental situations (Gralher et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This particularly holds with regard to complex and heterogeneous processes, such as infiltration and shallow subsurface flow in the vadose zone subject to strong gradients and fluxes of energy and matter, demanding stable isotope data with high spatial and temporal resolution to complement traditional observations. Instead, a major limitation to the extent and scope of stable isotope applications was imposed by the available techniques for sampling and analysis (e.g., Kerstel and Meijer, 2005;Helliker and Noone, 2010;Munksgaard et al, 2011). Conventionally, measurement of water stable isotopic composition was relatively labor-, time-, and cost-intensive and constrained to laboratory-bound analysis of previously collected and processed discrete samples based on gas source isotope ratio mass spectrometry (IRMS) (Horita and Kendall, 2004).…”
Section: T H M Volkmann and M Weiler: Pore Water Stable Isotopesmentioning
confidence: 99%
“…Other recent studies have used WS-CRDS for continuous determination of liquid water isotopic composition in laboratory experiments (Munksgaard et al, 2011;Herbstritt et al, 2012) and field applications (Munksgaard et al, 2012a, b) by direct intake and analysis of vapor diffused into a dry gas stream via a submerged semipermeable membrane body. A similar direct equilibration methodology can also be applied to determine the isotope signature of liquid pore water in situ as recently shown by Rothfuss et al (2013) in a sand beaker laboratory experiment.…”
Section: T H M Volkmann and M Weiler: Pore Water Stable Isotopesmentioning
confidence: 99%
See 1 more Smart Citation